2007
DOI: 10.3748/wjg.v13.i11.1715
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in Dutch patients with Hashimoto’s thyroiditis and vice versa

Abstract: AIM:To define the association between Hashimoto's thyroiditis and coeliac disease in Dutch patients. METHODS:A total of 104 consecutive patients with Hashimoto's thyroiditis underwent coeliac serological tests (antigliadins, transglutaminase and endomysium antibodies) and HLA-DQ typing. Small intestinal biopsy was performed when any of coeliac serological tests was positive. On the other hand, 184 patients with coeliac disease were subjected to thyroid biochemical (thyroid stimulating hormone and free thyroxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 54 publications
6
57
1
6
Order By: Relevance
“…This is somewhat lower than recent (smaller) studies which reported percentages between 2.7 and 4.8 (20)(21)(22)(23). We ruled out IgA-deficiency since Em and TTG test are an IgA-class test.…”
Section: Graves'contrasting
confidence: 55%
“…This is somewhat lower than recent (smaller) studies which reported percentages between 2.7 and 4.8 (20)(21)(22)(23). We ruled out IgA-deficiency since Em and TTG test are an IgA-class test.…”
Section: Graves'contrasting
confidence: 55%
“…However, there are a limited number of studies examining the prevalence of CD in children and adolescents with autoimmune thyroid disease. In studies conducted with adults, the prevalence of CD has been reported to be 10.8-3.3% in subjects with autoimmune thyroid disease (28)(29)(30). In studies conducted with children, the prevalence of CD has been reported to be 0.3-1.2% in healthy children and 1,3-6,5% in children and adolescents with a diagnosis of autoimmune thyroiditis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 104 Dutch patients with Hashimoto's thyroiditis, 8 (7.6%) were positive for TG autoantibodies and 5 (4.8%) had biopsies consistent with celiac disease. In this same report, researchers screened 184 patients with celiac disease and diagnosed hypothyroidism in 22 (12%) with 21% positive for antibodies associated with thyroid disease (28). This some observations holds true for pediatrics, in a series of 90 children with autoimmune thyroid disease, 7 (7.8%) were diagnosed with celiac disease after identification of positive EMA and small intestinal biopsy (27).…”
Section: Associated Conditions (Table 1)mentioning
confidence: 94%
“…Given the background prevalence of celiac disease of 1:100, there are populations that are at an increased risk for disease, including patients with type 1 diabetes (26), autoimmune thyroid disease (both hyper-and hypothyroidism) (27,28), relatives of patients with celiac disease (3) and type 1 diabetes and patients with Turner (29,30) and Down syndromes (31). Rates of celiac disease in these populations range from 5-10%.…”
Section: Epidemiology (Table 2)mentioning
confidence: 99%